In vitro conservation of apical meristem-tip of Melia azedarach L. (Meliaceae) under slow-growth conditions (with 1 table & 2 figures) - Scocchi, Adriana M. (2004)
Fil: Scocchi, Adriana M. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.